Protein kinase a‐dependent pSer675‐β‐catenin, a novel signaling defect in a mouse model of congenital hepatic fibrosis. Issue 5 (30th September 2013) - Spirli, Carlo; Locatelli, Luigi; Morell, Carola M.; Fiorotto, Romina; Morton, Stuart D.; Cadamuro, Massimiliano; Fabris, Luca; Strazzabosco, Mario
<x xml:space="preserve">Abstract</x> Genetically determined loss of fibrocystin function causes congenital hepatic fibrosis (CHF), Caroli disease (CD), and autosomal recessive polycystic kidney disease (ARPKD). Cystic dysplasia of the intrahepatic bile ducts and progressive portal fibrosis characterize liver pathology in CHF/CD. At a cellular level, several functional morphological and signaling changes have been reported including increased levels of 3′‐5′‐cyclic adenosine monophosphate (cAMP). In this study we addressed the relationships between increased cAMP and β‐catenin. In cholangiocytes isolated and cultured from Pkhd1del4/del4 mice, stimulation of cAMP/PKA signaling (forskolin 10 μM) stimulated Ser675‐phosphorylation of β‐catenin, its nuclear localization, and its transcriptional activity (western blot and TOP flash assay, respectively) along with a down‐regulation of E‐cadherin expression (immunocytochemistry and western blot); these changes were inhibited by the PKA blocker, PKI (1 μM). The Rho‐GTPase, Rac‐1, was also significantly activated by cAMP in Pkhd1del4/del4 cholangiocytes. Rac‐1 inhibition blocked cAMP‐dependent nuclear translocation and transcriptional activity of pSer675‐β‐catenin. Cell migration (Boyden chambers) was significantly higher in cholangiocytes obtained from Pkhd1del4/del4 and was inhibited by: (1) PKI, (2) silencing β‐catenin (siRNA), and (3) the Rac‐1 inhibitor NSC 23766. Conclusion: These data show that in fibrocystin‐defective cholangiocytes, cAMP/PKA signaling stimulates pSer675‐phosphorylation of β‐catenin and Rac‐1 activity. In the presence of activated Rac‐1, pSer675‐β‐catenin is translocated to the nucleus, becomes transcriptionally active, and is responsible for increased motility of Pkhd1del4/del4 cholangiocytes. β‐Catenin‐dependent changes in cell motility may be central to the pathogenesis of the disease and represent a potential therapeutic target. (Hepatology 2013;58:1713–1723)